STRUKTUR NARASI MEDIA GAME “WARCRAFT 3: REIGN OF CHAOS” Studi Pada Media Seni Kontemporer - Arief Ruslan (Avant Garde, 2014)
Warcraft 3: Reign of Chaos give the game more than just about victory or defeat, scoring, and rewards, but also offers a narrative (the story). This study will observe how the narrative structure built in showing progress through the story characterizations, plot, setting, also conflicts was meet by the characters in each game. The story shows that villainy does not always come suddenly, but can have a story structure with connecting causality so characterizations can be seen as an antagonist. With the analysis of the narrative structure of researchers see W3ROC provide insight to the players that villainy or goodness not only come from the same characteristic (static), but can also be of a different characteristic (dynamic). This means that the villainycan be show up from someone who is good or vice versa, through the events that passed by the figures.